The Relationship between Type 2 Diabetes Mellitus and the Success of Tuberculosis Treatment - Zhafira Isfy Adzkia; Friska Oktavrisa; Dwi Rosa Eka Agustina (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Tuberculosis (TB) is a major health burden in Indonesia, with comorbidity of type 2 diabetes mellitus (DM) further worsening treatment outcomes due to impaired immunity and drug effectiveness. This study aims to analyze the relationship between type 2 DM and TB treatment success at Waled Regional Hospital in Cirebon in 2024. Using a retrospective cross-sectional design based on secondary data from medical records and TB SITB in 104 pulmonary TB patients (total sampling of 507 cases, inclusion: complete records and completed treatment; exclusion: HIV/AIDS or resistant TB), univariate analysis described the demographic distribution, while bivariate analysis applied Fisher's Exact Test (p<0.05). The results showed a significant association (p=0.006), with treatment failure of 17.1% in TB-DM versus 1.6% in TB without DM, and treatment duration >6 months was dominant (70.7%) in TB-DM. Initial characteristics were elderly (46–55 years), housewives, females, elementary school education, and marital status. The study concluded that type 2 diabetes mellitus (DM) reduces TB treatment success through immunological and pharmacokinetic mechanisms; routine DM screening, strict glycemic control, and strengthening DOTS adherence are recommended for the 2030 TB elimination target